A systematic literature review of human papillomavirus vaccination strategies in delivery systems within national and regional immunization programs - Marisa Felsher; Meheret Shumet; Cristinela Velicu; Ya-Ting Chen; Kinga Nowicka; Magdalena Marzec; Gabriela Skowronek; Izabela Pieniążek (Human Vaccines & Immunotherapeutics)
The uptake of human papillomavirus (HPV) vaccine remains suboptimal despite being a part of routine vaccination within national immunization program(s). This indicates probable challenges with the implementation of HPV immunization program(s) in various countries. The objective of this systematic literature review (SLR) was to identify implementation strategies for HPV vaccination within national and regional immunization programs worldwide with an aim to provide guidance for countries targeting to increase their HPV vaccine coverage rate (VCR). A comprehensive literature search was conducted across Medline and Embase and included articles published between January 2012 and January 2022. Of the 2,549 articles retrieved, 168 met inclusion criteria and were included in the review. Strategies shown to improve HPV vaccination uptake in the reviewed literature include campaigns to increase community awareness and knowledge of HPV, health care provider trainings, integrating HPV vaccination within school settings, coordinated efforts via multi-sectoral partnerships, and vaccination reminder and recall systems. Findings may help national authorities understand key considerations for HPV vaccination when designing and implementing programs aiming to increase HPV VCR in adolescents.